Effects of Broad Spectrum Antibiotics on Measurement of Immunosuppressant Drugs - G, Ataman; Kirhan, Idris (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2021)
Background: Antibiotics used parenterally can affect blood drug level measurements, as measured in diagnostic tests. Objective: To investigate the effect of six different antibiotics commonly used in intensive care units on tacrolimus, sirolimus, everolimus and cyclosporin A levels measured by mass spectrometry. Methods: Ampicillin + sulbactam (AB1, IV, 1 g), imipenem + cilastatin sodium (AB2, IV, 500 mg), piperacillin + tazobactam (AB3, 4.5 g, IV), ertapenem (AB4, IV, 1 g), meropenem trihydrate (AB5, 500 mg, IV) and ceftriaxone (AB6, 1 g, IV) antibiotics were used for the interference assay. Measurements were performed on the Shimadzu 8045 (Japan) LC-MS/MS instrument. Bias values were calculated. Results: The least affected immunosuppressant was cyclosporine A (between -6.88% and 3.40%). The most affected were everolimus and sirolimus. Ertapenem caused negative interference on the level of everolimus at the rate of -27.34% and sirolimus at the rate of -26.79%. Piperacillin + tazobactam and imipenem + cilastatin sodium caused positive interferences on sirolimus at the rate of 24.24% and 22.73%, respectively. Ampicillin + sulbactam, meropenem trihydrate and ceftriaxone affected the sirolimus levels at lower rates (-4.49%, 5.93% and 9.86%). Everolimus levels deviated at the rate of -11.21% to -16.99% due to imipenem + cilastatin sodium, meropenem trihydrate and ceftriaxone. Conclusion: This study demonstrated the potential of antibiotic use affecting immunosuppressant levels. Antibiotic interference, especially in transplant patients, may cause erroneous immunosuppression, increasing the likelihood of rejection.
Keywords: sirolimus